PEDAGOGICAL FEATURES OF DEVELOPING CREATIVE COMPETENCE IN SCHOOL STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the relevance of the issue of training qualified personnel who can creatively approach the problems facing our state and society, a comparative analysis of scientific hypotheses given by researchers to concepts such as "creativity", "creative thinking", "creative approach" in order to fully understand the content and essence of the process of developing students' creative approach in technology lessons, and a practical-methodological approach to developing students' creative approach in technology lessons based on design methods scientific hypotheses about the significance and organizational and pedagogical foundations are presented.